Numerical simulation of a rapid fatigue test of high Mn-TWIP steel via a high cycle fatigue constitutive law. (March 2023) - Gonçalves, L.A.; Jiménez, S.; Cornejo, A.; Barbu, L.G.; Parareda, S.; Casellas, D.
Abstract: The generation of reliable data in the high cycle fatigue domain is crucial to support further metallurgic developments of fatigue optimized steel grades. Commonly employed for this aim, traditional standardized characterization methods are expensive and time-consuming. Thus, to circumvent these limitations, different accelerated fatigue testing methodologies have been proposed. In this work, the rapid fatigue test based on stiffness evolution is numerically reproduced using the finite element method for a specific grade of twinning-induced plasticity steel. A high cycle fatigue constitutive law grounded on the continuum damage mechanics framework is employed for this purpose. To adequately capture the material non-linear behavior observed in the experiments, a novel hardening–softening stress–strain curve for damage is proposed. The entire load history in the fatigue domain is modeled. A cycle-jump algorithm is used to improve the computational efficiency of the simulations. It is shown that a reduction of about 55% in the analysis elapsed time is reached by using this algorithm, while the result accuracy is maintained. Finally, the good agreement between numerical and experimental results, revealed by a maximum relative error smaller than 6.0%, evidences the potential of the present constitutive formulation to model the behavior of metals in the high cycle fatigue domain. Highlights: A high cycle fatigue constitutive model is used to reproduce a rapid fatigue test. An advance in time strategy is employed to improve the computational efficiency. The evolution of the fatigue damage is properly captured by the model. The material fatigue limit is accurately recovered by the model.